2017
DOI: 10.1590/1678-4324-2017160335
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Blue Crab Callinectes sapidus Rathbun, 1896 Bycatch in Artisanal Fisheries in Southern Brazil

Abstract: We evaluated the incidental catch of the blue crab in artisanal fisheries through the analysis of sex ratio, catch per unit effort, net positioning, and size in which the capture probability was 50% (P 50). The specimens were collected from 2011 to 2013 in the estuary of Patos Lagoon, southern Brazil. The analysis showed a higher occurrence of males. Variations in the catch per unit effort showed greatest abundance values close to the mouth of the estuary. Catch per unit effort was similar when comparing fishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The few records available for blue crab catch in the Patos Lagoon (Southern Brazil) show annual productivity of 400 tons per year, with maximum values recorded of ~1600 tons per year (Kalikoski & Vasconcellos, 2013). Values from 92.25 ± 49.59 to 125 ± 28.65 g h −1 have been reported as by-catch of shrimp fisheries with fyke nets, with highest catches in embayments from the mid to the upper estuary (Ruas et al ., 2017). However, recent research using local ecological knowledge revealed that largest CPUEs of blue crab decreased from ~10 kg net metre −1 day −1 in the 1980s to 2 kg net metre −1 day −1 in 2018 (Thykjaer et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The few records available for blue crab catch in the Patos Lagoon (Southern Brazil) show annual productivity of 400 tons per year, with maximum values recorded of ~1600 tons per year (Kalikoski & Vasconcellos, 2013). Values from 92.25 ± 49.59 to 125 ± 28.65 g h −1 have been reported as by-catch of shrimp fisheries with fyke nets, with highest catches in embayments from the mid to the upper estuary (Ruas et al ., 2017). However, recent research using local ecological knowledge revealed that largest CPUEs of blue crab decreased from ~10 kg net metre −1 day −1 in the 1980s to 2 kg net metre −1 day −1 in 2018 (Thykjaer et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, blue crabs (Callinectes spp.) are a relevant fisheries resources due its wide distribution and abundance in shallow waters of tropical and subtropical regions around the world, being mainly exploraited by the artisanal fishing through some fishing gears like crab traps and longlines (Bunnel et al, 2010;Anderson et al, 2011;Barletta et al, 2017;Mancinelli et al, 2017;Ruas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%